A novel interval dynamic reliability computation approach for the risk evaluation of vibration active control systems based on PID controllers - Wang, Lei; Liu, Jiaxiang; Yang, Chen; Wu, Di (Applied Mathematical Modelling, 2021)
PID control is widely used in vibration control systems. However, there are various uncertainties present in practical engineering, and the PID parameters obtained from a deterministic system may fail. Thus, reliability estimation is necessary to solve this problem. To avoid the disadvantages of traditional probabilistic methods, a non-probability based method to calculate time-dependent reliability is introduced to estimate the safety of a vibration active control system of based on PID controller performance. Next, the subinterval method is used to calculate a closed-loop response with large uncertainties and the first-passage theory is utilized to calculate the time-dependent reliability. Finally, one discrete mass-spring-damper system is analyzed for comparison with the collocation method and two panel structures (an elastic panel and a solar panel) are reliability evaluated to show the effects of the number of PID controllers and the displacement constraints.